Risk factors for failure of limb salvage among veterans with foot ulcers. Issue 5 (July 2022) - Trejo, Jonathan; Ryan, Emma; Khan, Fasiha; Iannuzzi, Nicholas; Chansky, Howard; Lack, William D.
Abstract: Background: There is limited available information to guide early discussions involving limb salvage for patients with non-traumatic foot ulcers. We hypothesized patient, wound and treatment factors identifiable at initial operative treatment would be associated with failure of attempted limb salvage. Methods: We retrospectively assessed United States military veterans treated operatively for non-traumatic foot ulcers at a Veteran's Administration (VA) hospital from 2008 to 2018. Cox proportional hazard analysis assessed for independent associations with eventual above ankle amputation. Results: Limb salvage failed for 52 of 461 patients (11.0%). Univariable associations included initial wound area ≥1 cm (p < .001), immediate TMA (p < .001), diagnosis of PVD (p < .001) or diabetes (p = .005), nonpalpable pulse (p = .006), CKD (p = .023), creatine ≥ 1.5 (p = .004), and HgA1c ≥ 6.2 (p < .001). Independent associations consisted of initial wound area ≥1 cm (HR 6.0, 95% CI 1.4–25.1, p = .014), immediate TMA (HR 3.5, 95% CI 1.9–6.4, p < .001), and PVD (HR 3.5, 95% CI 1.6–7.5, p = .001). When <2 risk factors were present, 99.1% and 96.8% retained their hindfoot at 5 and 10 years, respectively. However, this decreased to 87.3% and 80.1% with two risk factors and fell to 63.3% and 43.3% with three risk factors. Conclusion: Failure of limb salvage was increasingly likely as the number of identified independent risk factors increased. These results may assist in prognostication and shared decision making between patients and providers. Level of evidence: Prognostic, Level III.